2020
DOI: 10.1177/0886260520966669
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Victimization, Psychopathy, and the Acceptance of Rape Myths

Abstract: Rape myths are attitudes that implicitly and explicitly blame victims for their own sexual victimization. Greater adherence to rape myths is linked to several negative outcomes, including the neutralization of gender-based violence and the perpetration of sexual violence. Few studies have considered how previous life experiences and individual-level traits influence the development and greater adherence to rape myths. The current study examines how traits associated with the three-factor model of psychopathy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
(153 reference statements)
1
6
0
2
Order By: Relevance
“…The authors used structural equation modeling to examine these relationships and found that the Callous Affect scale of the SRP-III (Self-report Psychopathy, 3 rd edition) and exposure to violence in childhood were significantly related to increased rape myth acceptance, further indicating the importance of personality variables (including stable psychopathic characteristics) in the explanation of sexual violence. In a recent and similar study, Cooke and colleagues (2022) examined how the personality traits associated with the three-factor model of psychopathy and adherence to traditional gender roles mediated the relationship between prior victimization and endorsement of rape myths in a sample of college men and women. Their path model indicated that prior experiences of victimization were related to increased egocentric psychopathic traits, which were in turn related to the acceptance of rape myths later in life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors used structural equation modeling to examine these relationships and found that the Callous Affect scale of the SRP-III (Self-report Psychopathy, 3 rd edition) and exposure to violence in childhood were significantly related to increased rape myth acceptance, further indicating the importance of personality variables (including stable psychopathic characteristics) in the explanation of sexual violence. In a recent and similar study, Cooke and colleagues (2022) examined how the personality traits associated with the three-factor model of psychopathy and adherence to traditional gender roles mediated the relationship between prior victimization and endorsement of rape myths in a sample of college men and women. Their path model indicated that prior experiences of victimization were related to increased egocentric psychopathic traits, which were in turn related to the acceptance of rape myths later in life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The failure to recognize the pervasiveness and severity of sexual assaults is, in part, due to widespread misinformation about sexual assault victims, perpetrators, and the act of rape. Rape myths consist of various beliefs that blame victims, absolve the perpetrator, and minimize adverse consequences experienced by victims (Cooke et al., 2020; Payne et al., 1999). Previous research has found that ideological beliefs such as rape myth acceptance contribute to the likelihood of sexual harassment (Begany & Milburn, 2002).…”
Section: Rape Myth Acceptancementioning
confidence: 99%
“…Previous research has found that ideological beliefs such as rape myth acceptance contribute to the likelihood of sexual harassment (Begany & Milburn, 2002). Additional research has also shown that underlying personality characteristics as well as traditional gender role attitudes, and endorsement of hostile and benevolent sexism are associated with a greater likelihood of endorsing rape myths (Cooke et al., 2020; Abrams et al., 2003). Furthermore, Chapleau and Oswald (2014) found that rape myths were linked with reduced moral outrage to injustice, which can reduce victims and bystander's action against the sexual violence.…”
Section: Rape Myth Acceptancementioning
confidence: 99%
“…The acceptance of rape myths functions to normalize and minimize the perception of harm resulting from sexual violence, further perpetuating sexual violence against women (Payne et al., 1999). Furthermore, endorsement of traditional gender role attitudes and hostile and benevolent sexism are all associated with a greater likelihood of endorsing rape myths (Abrams et al., 2003; Chapleau et al., 2007; Cooke et al., 2020; Glick & Fiske, 1997). While there is a limited amount of research relating feminist ideologies to rape myth acceptance, one study (Holland et al., 2020) examined how feminist beliefs and rape myth acceptance in college resident assistant's willingness to provide help for victims of sexual assault.…”
Section: Introductionmentioning
confidence: 99%